Anterior cruciate ligament injuries in young females playing soccer at senior levels - Soderman, K.; Pietila, T.; Alfredson, H.; Werner, S. (Scandinavian Journal of Medicine & Science in Sports, 2002)
The aim of this investigation was to study the consequences of anterior cruciate ligament injuries in female soccer players. Special interest was focused on young female soccer players (< 16 years) sustaining anterior cruciate ligament injuries when playing at a senior level, which means playing together with players 19 years or older. In Sweden, all players belonging to an organized soccer club are insured by the same insurance company, the Folksam Insurance Company. Data of all soccer-related knee injuries in females reported to the Folksam Insurance Company between 1994 and 1998 were collected. A questionnaire was sent to 978 females who were registered to have sustained a knee injury before the age of 20 years. The response rate was 79%. Three hundred and ninety-eight female soccer players who had sustained an anterior cruciate ligament injury before the age of 19 years were analysed. Most of their anterior cruciate ligament injuries had been diagnosed using arthroscopy or magnetic resonance imaging (84%). Thirty-eight percent of the players had been injured before the age of 16 years. Of these, 39% were injured when playing in senior teams. When playing in senior teams 59% of the players below the age of 16 years and 44% of the players 16 years or older sustained their ACL injuries during contact situations. At the time of this investigation (2-7 years after the anterior cruciate ligament injury), altogether 78% (n = 311) reported that they had stopped playing soccer. The most common reason (80%) was symptoms from their anterior cruciate ligament-injured knee. It appears that many young female soccer players injure their anterior cruciate ligament when playing at a senior level. Therefore, we suggest that female soccer players under the age of 16 years should be allowed to participate only in practice sessions but not games at a senior level.